2020
DOI: 10.3390/ma13041011
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Conductivity Properties of Hemp–Lime Composite Material Used in Single-Family Buildings

Abstract: The main goal of the paper is to calculate the heat conductivity for three experimental hemp–lime composites used for structural construction purposes with the use of the experimental stand inside two compartments. Due to current construction trends, we are constantly searching for eco-friendly materials that have a low carbon footprint. This is the case of the analyzed material, and additional thermographic heat distribution inside the material during a fire resistance test proves that it is also a perfect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…The study proposed by Curto et al [ 55 ] has shown that the increase in the percentage of hemp shives in a mixture of lime and water decreases the thermal conductivity and increases the sound absorption values. Pochwała et al [ 56 ] found for a hemp-lime composite that the thermal conductivity ranged from 0.038–0.055 W/(m·K), depending on how much the shiv was compacted and what mixing method was applied. These properties are attributable to the porosity between the particles (about 80%) and the appearance of a porous surface [ 57 ].…”
Section: State-of-artmentioning
confidence: 99%
“…The study proposed by Curto et al [ 55 ] has shown that the increase in the percentage of hemp shives in a mixture of lime and water decreases the thermal conductivity and increases the sound absorption values. Pochwała et al [ 56 ] found for a hemp-lime composite that the thermal conductivity ranged from 0.038–0.055 W/(m·K), depending on how much the shiv was compacted and what mixing method was applied. These properties are attributable to the porosity between the particles (about 80%) and the appearance of a porous surface [ 57 ].…”
Section: State-of-artmentioning
confidence: 99%
“…The aim of the present work is to reduce the thermal conductivity or, in other words, to enhance the heat insulating capability of the lime mortar. A common practice to achieve this goal is the addition of filling particles of organic/vegetal origin, such as cork [ 6 ], hemp [ 7 , 8 ], olive stone [ 9 ], textile waste [ 10 ], straw [ 11 ], coconut [ 12 ], etc. The strategy of the present study is the addition of ceramic submicron particles, whose use and chemical composition is fully compatible with an ecological concept from the point-of-view of generating future, harmless waste for soil and subsoil.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies based on the same topic in the literature [20][21][22][23]. Hamzaoui et al recently investigated the mechanical performance of mortar, considering the addition of hemp [20].…”
Section: Introductionmentioning
confidence: 99%
“…The heat conductivity of a hemp-lime composite material has been recently assessed by Pochwala et al, reporting interesting values for the building insulation [22].…”
Section: Introductionmentioning
confidence: 99%